2020
DOI: 10.1002/cb.1833
|View full text |Cite
|
Sign up to set email alerts
|

How values of individualism and collectivism influence impulsive buying and money budgeting: the mediating role of acculturation to global consumer culture

Abstract: This study examined the effects of individual‐level cultural values of individualism and collectivism on impulsive buying and money budgeting and the mediating role of acculturation to global consumer culture. By applying the person‐environment fit theory and acculturation theory, we argue that people who hold cultural values congruent with the culture they come into contact with are more likely to acculturate to it, and that those who acculturate to global consumer culture (GCC) are more likely to display con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 109 publications
1
21
0
1
Order By: Relevance
“…As their interpersonal ties in the hotel increase, frontline employees tend to receive significant social support in the hotel, which places them in a good position to acquire greater work resources to enhance their life satisfaction. This was unsurprising because individuals from collectivistic cultures, such as Ghana, put significant premium on relational ties (Czarnecka et al, 2020). However, it was found that sacrifice and fit did not impact frontline hotel employees’ life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…As their interpersonal ties in the hotel increase, frontline employees tend to receive significant social support in the hotel, which places them in a good position to acquire greater work resources to enhance their life satisfaction. This was unsurprising because individuals from collectivistic cultures, such as Ghana, put significant premium on relational ties (Czarnecka et al, 2020). However, it was found that sacrifice and fit did not impact frontline hotel employees’ life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Given the centrality of culture in understanding consumption-related preferences and behaviour (McCracken, 1986), international marketing literature includes a number of frameworks for measuring a market's level of global consumer orientation and the acculturation to the global consumer culture. Appadurai's (1990) Whilst several studies have endeavoured to ascertain the acculturation to the global consumer culture in developed and emerging economies (Alden et al, 1999;Alden et al, 2006;Cleveland et al, 2013;Durvasula & Lysonski, 2016;Czarnecka et al, 2020), as well as the acculturation of minority groups of immigrants within developed countries (Der-Karabetian & Ruiz, 1997;Mathur et al, 2008;Westjohn et al, 2012), and susceptibility to the global consumer culture (Zhou et al, 2008), there remains a lack of research of this phenomenon on the African continent, particularly in South Africa. Furthermore, while there are overtures that young adults tend to have a stronger global consumer orientation than their older counterparts (Durvasula & Lysonski, 2008;Mathur et al, 2008;Gupta, 2013), there are only a few studies focusing specifically on their acculturation to the global culture (Wee, 1999;Carpenter et al, 2012;Durvasula & Lysonski, 2016;Frank & Watchravesringkan, 2016).…”
Section: Journal Of Contemporarymentioning
confidence: 99%
“…A global consumer orientation refers to the consumption preference for brands, products and services that are similarly perceived by consumer across the globe (Alden et al, 1999;Steenkamp, 2019;Czarnecka et al, 2020). This global consumer culture is driven by the forces of globalisation, which include inter alia global media, digital platforms, international transportation, multi-national organisation marketing, global trade and international payment methods (Alden et al, 2006;Steenkamp, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the role of culture in the process of impulsive buying in ms–commerce. Although many studies have shown that cultural orientation can play a vital role in consumers' impulse buying (Czarnecka et al , 2020; Miao et al , 2019), they have collected certain cultural dimensions and used them only as independent variables. Those studies can be helpful in understanding how cultural dimensions can influence impulse buying, but they do not help us assess how certain relationships differ in various espoused cultural dimensions.…”
Section: Introductionmentioning
confidence: 99%